A new book of Serbian encyclopaedia: a step forward in the revival of national self-respect - Ocić, Dejana (Sociološki pregled, 2022)
When browsing through the recently published second book of the third volume of Serbian Encyclopaedia, which has been published since 2010, inevitable questions arise about the role and importance of each of those books and the entire project to the culture of the Serbian nation. By its basic characteristics, Serbian Encyclopaedia has the potential to open, awaken or refresh knowledge and memory of the facts about Serbian history, as well as of its up-to-dateness and perspective, i.e. to recover the national self-awareness that is so necessary to Serbs, which is not only one of the necessary prerequisites for national self-respect, but also a basic presupposition of survival and development.
Keywords: Serbian Encyclopaedia; national project; national self-respect; entries; illustrative material